Evaluation and optimisation of environmentally friendly aircraft propulsion systems - Celis, Cesar (Cranfield University, 2010)
In this globalised world where the efficient transportation of people and goods greatly contributes to the development of a given region or country, the aviation industry has found the ideal conditions for its development, thereby becoming in one of the fastest growing economic sectors during the last decades. The continuing growth in air traffic and the increasing public awareness about the anthropogenic contribution to global warming have meant that environmental issues associated with aircraft operations are currently one of the most critical aspects of commercial aviation. Several alternatives for reducing the environmental impact of aircraft operations have been proposed over the years, and they broadly comprise reductions in the number of aircraft operations, changes in the type of aircraft, and changes in the aircraft operational rules and procedures. However, since the passenger traffic is expected to increase over the next years, only the last two options seem to be the most feasible solutions to alleviate the problem. Accordingly, the general aim of this research work is to develop a methodology to evaluate and quantify aircraft/engines design trade-offs originated as a consequence of addressing conflicting objectives such as low environmental impact and low operating costs. More specifically, it is an objective of this work to evaluate and optimise both aircraft flight trajectories and aircraft engine cycles taking into account multidisciplinary aspects such as performance, gaseous emissions, and economics. In order to accomplish the objectives proposed in this project, a methodology for optimising aircraft trajectories has been initially devised. A suitable optimiser with a library of optimisation algorithms, Polyphemus, has been then developed and/or adapted. Computational models simulating different disciplines such as aircraft performance, engine performance, and pollutants formation, have been selected or developed as necessary. Finally, several evaluation and optimisation processes aiming to determine optimum and ‘greener’ aircraft trajectories and engine cycles have been carried out and their main results summarised. In particular, an advanced, innovative gaseous emissions prediction model that allows the reliable calculation of emissions trends from current and potential future aircraft gas turbine combustors has been developed. When applied to a conventional combustor, the results showed that in general the emission trends observed in practice were sufficiently well reproduced, and in a computationally efficient manner for its subsequent incorporation in optimisation processes. For performing the processes of optimisation of aircraft trajectories and engine cycles, an optimiser (Polyphemus) has also been developed and/or adapted in this work. Generally the results obtained using Polyphemus and other commercially available optimisation algorithms presented a satisfactory level of agreement (average discrepancies of about 2%). It is then concluded that the development of Polyphemus is proceeding in the correct direction and should continue in order to improve its capabilities for identifying and efficiently computing optimum and ‘greener’ aircraft trajectories and engine cycles, which help to minimise the environmental impact of commercial aircraft operations. The main contributions of this work to knowledge broadly comprise the following: (i) development of an environmental-based methodology for carrying out both aircraft trajectory optimisation processes, and engine cycle optimisation-type ones; (ii) development of both an advanced, innovative gas turbine emissions prediction model, and an optimiser (Polyphemus) suitable to be integrated into multi-disciplinary optimisation frameworks; and (iii) determination and assessment of optimum and ‘greener’ aircraft trajectories and aircraft engine cycles using a multi-disciplinary optimisation tool, which included the computational tools developed in this work. Based on the results obtained from the different evaluation and optimisation processes carried out in this research project, it is concluded that there is indeed a feasible route to reduce the environmental impact of commercial aviation through the introduction of changes in the aircraft operational rules and procedures and/or in the aircraft/engine configurations. The magnitude of these reductions needs to be determined yet through careful consideration of more realistic aircraft trajectories and the use of higher fidelity computational models. For this purpose, the computations will eventually need to be extended to the entire fleet of aircraft, and they will also need to include different operational scenarios involving partial replacements of old aircraft with new environmentally friendly ones.